Influence of ball milling process on microstructure, mechanical and thermal expansion properties of ZrMgMo3O12/Al-40Si composites. (June 2022) - Song, Panying; Xie, Kun; Yang, Junrui; Jiang, Dandan; Liu, Zhongxia; Zhang, Jianming; Zhang, Guopeng; Cai, Bin
Abstract: In this study, ZrMgMo3 O12 /Al-40Si (ZMMO/Al-40Si) composites with 15 wt% ZrMgMo3 O12 were fabricated by ball milling-vacuum hot pressing (VHP) processes. The effect of ball milling processes on the microstructure, compressive properties and coefficient of thermal expansion (CTE) of the composites were investigated. It is found that ball milling treatments of mixed ZMMO/Al-40Si powders refine the particles of ZMMO reinforcements and primary Si in ZMMO/Al-40Si composites and improve the distribution of ZMMO reinforcements in α-Al matrix, resulting in the increase of the compressive strength and the decrease of the CTE of ZMMO/Al-40Si composites. The highest compressive yield strength of 430.82 MPa and the lowest CTEs of 5.8 × 10 −6 /°C (RT – 400 °C) are obtained after ball milling for 8 h at 250 rpm, increasing by 145.9% and decreasing by 61.3% respectively compared with the compressive yield strength and CTE of Al-40Si alloy. Among the reinforcements commonly used in aluminum matrix composites, ZMMO reinforcement has the highest reduction efficiency for CTE of ZMMO/Al-40Si composite. The application of high-energy ball milling to refine the microstructure is a promising method that can simultaneously increase the strength and reduce the CTEs of ZMMO/Al-40Si composites. Highlights: The ZMMO increases the compressive yield strength (σyc) and decreases the CTE of Al-40 Si. The ball milling processes refine the particles of ZMMO and primary Si. The high energy ball milling increases σyc and decreases CTE of composites. The σyc and CET increased by 145.94% and reduced by 61.3% respectively. Improving CTE matching between ZMMO and Al matrix is critical to reduce CTEs of composites.